Etika dalam kepemilikan dan pengelolaan harta serta dampaknya terhadap ekonomi Islam - Efendi, Nur; Nurhasanah, Neneng; Saripudin, Udin (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The issue of ownership is regulated extensively in Muamalah fiqh in the fields of Al-Mal (property) and Al-Milk (property). Regarding ownership, it is regulated so that there is no violation of one's rights by other individuals, because humans have a tendency towards material things. Islamic recognition of property rights is reflected in the concept of haq al-adami, protection of individual ownership is also regulated in Islam by determining sanctions against people who rob them. This study aims to determine how the concept of Islam in regulating individual ownership rights and how the ethics that must be obeyed in the context of property ownership. This study uses secondary data with data collection methods carried out by means of library research, namely by studying, exploring and citing theories or concepts from a number of literatures such as journals, books, and others. The results of the study that the rules of ownership in Islam have implications for the potential for Islamic economic development, good application of the rules of ownership can have implications for reducing the amount of poverty and economic equity in society.